Blood lead level and related factors in ADHD patients of Loghman Hakim Hospital in 2016- 2017 - Rezayi, Alireza; Farnaghi, Fariba; Sadeghian, Shiva; Hassanian-Moghaddam , Hossein; Zamani, Nasim; Gachkar, Latif; Gholami, Narges (Researcher Bulletin of Medical Sciences, 2020)
Introduction: Lead is a highly neurotoxic metal mainly in early life. In this study we investigate blood lead level (BLL) in children with attention deficit/ hyperactivity disorder (ADHD) and some related factors mainly opium exposure, as a source of lead exposure in recent years in Iran. Materials and Methods: In this cross-sectional descriptive study children & adolescents aged < 18 years in Child Neurology Clinic of Loghman Hakim hospital with ADHD criteria according to DMS-V in Tehran-Iran were studied. Lead Care II checked BLLs using 0.5-milliliter heparinzed venous blood. Demographics characteristic and some related factors such as old housing, parents’ job, pica, opium exposure were asked and analyzed. Results: Fifty-one children and adolescents <18 years, 25.5% female and 74.5% male with mean ages of 71.4+30.3 months entered the study. Mean BLL was 6.34+2.63 µg/dl. The mean BLL in 100 normal children in Loghman Hakim hospital was 3.4 µg/dl. Mean BLL was 57/6 µg/dl in boys and60/6 µg/dl in girls, (p=0.973). Also, the difference in mean BLLs were not significant in terms of living place, sex, age, pica and parents job. Totally, 43 patients (84.3%) of the study samples had BLL ≥5 µg/dl. The highest blood lead level in our patient was 20.1 µg/dl. Eighteen (32.7%) of our patients have positive history for opium exposure in their family that BLL in this group was 5.84 µg/dl in comparison 6.95 µg/dl in cases with no opium exposure, that there were not statistically significant. (p=0.148) Conclusion: Based on the results of our study, clinicians are encouraged to take accurately attention about possible lead exposure and to rule out environmental hazards when evaluating for ADHD, particularly in young children and laboratory investigation for this toxin in high-risk cases and further researches recommended